Does The Lack of Information and Guidance About Career Opportunities in the Science Field Cause Students to Lose Interest in Choosing This Stream? - Han , Shin Ni; Jamal, Siti Najihah; Ibrahim, Norhasniza; Ong, Shi Ting; Tan, Sok Jing; Surif, Johari (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
This study investigates whether the lack of career information and guidance contributes to students losing interest in the science stream. Conducted among 30 Form 4 Science stream students in Johor Bahru, the research employed a quantitative survey to assess perceptions of career guidance, access to information, and its influence on interest in science-related careers. The findings reveal that while most students (83.3%) remain interested in pursuing science-related professions, inadequate career counselling leads to uncertainty and reduced confidence in making informed career decisions. Many students rely on the internet for career information, which may expose them to misinformation and further confusion. Although a lack of guidance does not directly diminish interest in science, it significantly affects students’ self-assurance in choosing suitable science-based pathways. Respondents emphasized the importance of structured career counselling, career talks, and exposure to professionals in science fields. Such initiatives help clarify job scopes, required qualifications, and available opportunities, thus supporting better career planning. The study concludes that strengthening career guidance in schools is essential to ensure students are well-informed and motivated to pursue careers in science. Addressing this gap is crucial for Malaysia’s efforts to boost STEM enrolment and develop a skilled workforce for future economic growth.